Fuzzy self organizing map ellipse patch evaluation model for technical systems. (October 2018) - Yangxi, Liu; Xiangle, Zhang
Abstract: This paper proposes an evaluation method of vocational and technical course reform using the minimum-rule self-organizing maps ellipse fuzzy-patch evaluation model. First, it analyses the vocational and technical education course system reform evaluation model. Considering teachers and experts an evaluation model and a determination process of index weight is obtained. Then the situation in which many self-organizing maps nodes may cause complex models and overfitting is identified. Then we adopt the Pearson correlation coefficient to process determination problems of optimal self-organizing maps grid size and provides suggestions. Then we estimate the ellipse fuzzy patch construction method based on improved Gaussian membership for computing relevant data. Finally, we verify the effectiveness of the method via simulation testing.